EVALUATION OF EXTRACTS AGAINST PLANT ASPERGILLUS NIGER SCLEROTIUM ROLFSII AND CAUSING COLLAR ROT AND SEED ROT IN CHICKPEA (Journal of Plant Disease Sciences, 2017)
acetone, chloroform, The fungitoxic effects of different solvents viz., distilled water, ethanol and methanol extractions of two weeds namely, Parthenium hysterophorus Datura stramonium in vitro Sclerotium and were evaluated against rolfsii Aspergillus niger and , the causal agents of collar rot and seed rot of chickpea, respectively. Maximum extraction yield (8.46%) of whole plant P. hysterophorus extract was obtained in methanol solvent and minimum in chloroform (3.45%), while in case of extract more extraction yield was obtained in D. stramonium methanol (10.70) and less 6.40% in acetone. Among all the solvent extracts, methanol extract of had potential antifungal activity against P. hysterophorus S. rolfsii A. niger and .
Keywords: Solvent extracts antifungal activity, stramonium, , D. P. hysterophorus, S. rolfsii, A. niger